Novel skin chamber for rat ischemic flap studies in regenerative wound repair. Issue 1 (December 2016) - Hsueh, Yuan-Yu; Wang, Duo-Hsiang; Huang, Tzu-Chieh; Chang, Ya-Ju; Shao, Wei-Chi; Tuan, Tai-Lan; Hughes, Michael; Wu, Chia-Ching
Abstract Background In plastic surgery, skin flap is an important approach to reconstructive wound repairs. The rat dorsal skin flap is a clinically relevant and popular animal model to investigate and evaluate flap survival and necrosis. Nonetheless, flap survival is often unstable with unpredictable outcomes, regardless of previous attempts at design modification. Methods & Results In the present study, we report a novel flap chamber that provides stable and reproducible outcomes by separating the dorsal skin flap from its surrounding skin by in situ immobilization. The flap chamber blocks circulation that disturbs flap ischemia from both basal and lateral sides of the flap tissue. Demarcation of skin necrosis is macroscopically evident on the flap and supported by distinct changes in histological architecture under microscopic examination. The utility of the novel skin flap chamber is further proven by applying it to the examination of flap survival in streptozotocin-induced diabetic rats with an increase in skin necrosis. The flap chamber also affords size modifications where a narrower flap chamber increases ischemia and provides manipulable therapeutic windows for studying cell therapies. Accordingly, intradermal injection of endothelial cells 3 days before flap ischemia significantly increases the survival of skin flaps. Conclusions The novel flap chamber not only may stabilize the skin flap and provide reproducible outcomes that overcome the shortfalls of the traditional ischemic flap but also may afford size modifications that support research designs and test therapeutic approaches to regenerative repair.